Protective Effects of Thymoquinone and Melatonin on Intestinal Ischemia-reperfusion Injury - Tas, Ufuk; Ayan, Murat; Sogut, Erkan; Kuloglu, Tuncay; Uysal, Murat; Tanriverdi, Halil I.; Sarsilmaz, Mustafa (Medknow Publications & Media Pvt Ltd, 2015)
Background/Aim: In the present study, we aimed to compare the potential protective effects of thymoquinone and melatonin by using equivalent dose, on oxidative stress-induced ischemia-reperfusion (IR) injury in the intestinal tissue of rats. Materials and Methods: The study was performed using 32 male Wistar-Albino rats (weighing 180-200 g) randomly divided into four groups: Group I, sham group; Group II, IR group; Group III, IR with melatonin group; and Group IV, IR with thymoquinone group. After laparotomy, ischemia and reperfusion were performed for 60 and 120 min, respectively, on all the groups. Intestinal tissue sections were stained using routine histological methods and examined under the light microscope. In addition, the sections were immunohistochemically stained using the TUNEL method for determination of apoptosis. Superoxide dismutase (SOD) activity, glutathione peroxidase (GSH-Px) activity, and malondialdehyde (MDA) levels in the intestinal tissue were also measured. Results: The IR group had significantly elevated tissue SOD activity, GSH-Px activity, and MDA levels compared with the sham group. Administration of thymoquinone and melatonin efficiently reduced these increases. Statistically significant number of apoptotic cells was observed in the intestinal tissue of IR group rats compared with the sham group. Treatment with thymoquinone and melatonin markedly reduced the number of apoptotic cells. Conclusion: The effects of melatonin and thymoquinone on IR-induced oxidative stress in rat intestines were similar. Our findings suggest that melatonin and thymoquinone protect against IR-induced injury to intestinal tissues.
Keywords: Intestine; ischemia-reperfusion injury; melatonin; oxidative stress; thymoquinone